PERAN GURU DALAM MENGINTEGRASIKAN NILAI-NILAI KARAKTER DALAM PROSES PEMBELAJARAN BAHASA INDONESIA - Cane Widya Agustina, Vinutria, Afroha Maulida Nisrina, Aprilia Nur Azizah (Universitas Islam Malang, 2021)
A teacher is a teacher as well as a mentor for each student. The role of teachers in education is certainly very important. The role of teachers is needed in the educational process, because the role of teachers who educate, teach, guide, train and provide assessment and evaluation to students, which is an important aspect in the process of quality level and quality of education. In addition, it plays an important role in the process of character formation, personality and intellectual aspects. With the role of catalysts, evaluators, inspirations and motivators are expected to integrate character values in the learning process of Indonesian language. Therefore, the role of teachers in shaping the character of students determines the quality and development of students. In fact, a teacher is required to create a comfortable and safe atmosphere in order to act as a teacher who integrates character values through catalyst teachers, evaluators, inspirations and motivators. Because the role of teachers in indonesian language learning is to bring students to speak good and correct Indonesian language.